The evaluation of radiologic methods for access guidance in percutaneous nephrolithotomy: a systematic review of the literature - Breda, Alberto; Knoll, Thomas (Scandinavian journal of urology, 2018)
Introduction: Percutaneous nephrolithotomy (PNL) is the treatment of choice for larger and complex renal calculi. First step in performing PNL is to obtain access to the renal cavity using either fluoroscopy or ultrasound (US) guidance or a combination of both. Which guiding method to choose is controversial? A systematic review of the literature was performed comparing image guidance modalities for obtaining access in PNL.Evidence acquisition and synthesis: A PubMed, Scopus and Cochrane search for peer-reviewed studies was performed using the keywords “ultrasound” AND “fluoroscopy” AND “Percutaneous nephrolithotomy”. Eligible articles were reviewed according to PRISMA criteria. Two hundred and forty records were identified using the keywords. Of these twelve studies were considered relevant.Results: US guidance seems to be associated with a slightly lower complication rate, which may be related to fewer puncture attempts needed for obtaining access and to better peri-renal organ visualization. On the other hand, US-guidance alone needs the adjunct of fluoroscopy in a significant number of cases for achieving access. Stone free rate (SFR) was comparable between groups. Using US for renal access unequivocally reduces radiation exposure.Conclusion: Current evidence indicates that both fluoroscopy and US guidance may be successfully used for obtaining percutaneous renal access. Combining the image-guiding modalities - US and fluoroscopy - seems to increase outcome in PNL both with regard to success in achieving access and reducing complications. Furthermore, including US in the access strategy of PNL reduces radiation exposure to surgeon and staff as well as patients.
Published online: 12 Nov 2017
Gesehen am 15.02.2021